EFEKTIFITAS APLIKASI KRESNA SEBAGAI MEDIA PEMBELAJARAN BERBASIS APLIKASI DIGITAL DALAM MENINGKATKAN PEMAHAMAN MENGENAL ANGKA DAN OPERASI HITUNG MATA PELAJARAN MATEMATIKA PADA ANAK TUNA GRAHITA SUATU TINJAUAN PSIKOLOGI - Rangga Wardhana, Lauren David; Rosidah, Indah; Juwarini Prihastiwi, Wiwik (Jurnal Ilmiah Penelitian Psikologi, 2022)
This study aims to determine the effectiveness of learning mathematics based on the digital application "Kresna" on number recognition and arithmetic operation ability in mathematics subjects for mild mental retardation at the elementary school level. The research subjects were 3 light mild mental retardation students at the elementary school level. The design of this study was an experimental one group pretest and posttest. The purpose of the pretest was to determine the initial ability of the research subject students and as a comparison group, while the posttest was carried out with the aim of knowing the final ability of the research subject after the treatment was given. The implementation of the treatment carried out in this study was to provide learning using the Krishna digital application which was carried out for 4 face-to-face with. Learning is done by guiding and helping students to enter the Kresna application and solve every problem that exists at each level (easy, medium, and difficult) number recognition and arithmetic operations which include addition, subtraction and multiplication. The researcher also helps students in working on the story problem models contained in social experiences that discuss addition and subtraction, as well as on the quiz feature, which is a feature that discusses a review of the collection of material from the previous feature. Instruments for measuring pretest and posttest are arranged in the form of questions based on the grid of learning materials contained in each feature in the Kresna application. The results of statistical tests using t-test showed that the average pretest was 73,333 and the average posttest was 93,3333 and p = 0,074. Based on the results of the t-test, it can be concluded that there is no significant difference between the achievement of understanding numbers and the ability of arithmetic operations on the research subjects. However, when viewed from the pretest and posttest scores, each individual research subject showed an increase and exceeded the learning mastery value limit (score 70). Suggestions for further researchers are expected to create digital application-based learning media with 3-dimensional images or videos, so that it can make it easier for elementary school students to have more concrete knowledge and increase the number of meetings and increase the number of research subjects.